Humidity-robust scalable metal halide perovskite film deposition for photovoltaic applications. Issue 47 (25th November 2020) - Perini, Carlo Andrea Riccardo; Reddy Pininti, Anil; Martani, Samuele; Topolovsek, Peter; Perego, Andrea; Cortecchia, Daniele; Petrozza, Annamaria; Caironi, Mario
Abstract : We propose an intermediate-mediated perovskite deposition route based on acetonitrile, working in a broad range of humidity levels and compatible with large-area deposition, thus more amenable to industrialization. Abstract : Organic–inorganic perovskite photovoltaics have now achieved power conversion efficiencies at par with silicon devices on a lab-scale. To enable industrial application of the technology, developing a perovskite deposition route compatible with scalable, large-area deposition methods, which exploits safer processing solvents and is robust to variations of the processing parameters, particularly humidity, is highly demanded. To satisfy such constraints altogether, here we introduce a lead iodide–hydroiodic acid–water precursor (PbI2 –HI–H2 O) that enables the scalable deposition of methylammonium lead triiodide (MAPbI3 ) films from a safer solvent (acetonitrile – ACN) in a wide range of high moisture levels, spanning from 50 to 80% relative humidity. When exposed to a methylamine (MA) gas flow the PbI2 –HI–H2 O precursor readily converts to specular perovskite films. If heated, the PbI2 –HI–H2 O film can be easily reverted to PbI2, further enabling the implementation of two step deposition methods. Our process was tested in an inverted solar cell configuration achieving stabilized power conversion efficiencies of 14% with minimal annealing requirements. Our findings demonstrate an appealing route for a large-area compatible manufacturing of hybrid perovskite photovoltaics in air, at high moisture levels, based on solvents of reduced hazard.